Barbara Lippert – Gaby Umbach: The Pressure of Europeanisation: From post-communist state administrations to normal players in the EU system. - Leona Šteigrová (Czech Journal of International Relations, 2006)
Barbara Lippert – Gaby Umbach: The Pressure of Europeanisation: From post-communist state administrations to normal players in the EU system. 1. Aufl. Institut für Europäische Politik, Europäische Schriften 82. Baden-Baden: Nomos, 2005, 203 stran, ISBN 3-8329-1230-4 (signatura knihovny ÚMV 51 960).